STUDY OF THE INFLUENCE OF REGIONAL DEVELOPMENT FACTORS ON THE FORMATION OF THE STUDENT CONTINGENT - Chang, Liu; Mamonov, К.; Kanivets, О. (Municipal economy of cities. Series: «Economy science», 2023)
The relevance of the study of the influence of factors of regional development on the formation of the contingent of students has been proven. The purpose of the study is to determine the cause-and-effect relationships between the number of students in higher education institutions and the regional development indicator. To achieve the goal, the following tasks are solved: characteristics of mathematical tools to ensure the educational process; development of a mathematical model of the influence of the gross regional product index on the number of students in higher education institutions. Proposed directions Mathematical modeling is implemented through the prism of the relevant stages: formation of information and analytical support regarding the factor of formation of the contingent of students by region and the integral indicator of regional development; application of mathematical modeling methods in relation to establishing the influence of the factor on the integral indicator; development of mathematical models of the influence of the factor on the integral indicator of regional development; determination of criteria for the adequacy of mathematical models; interpretation of the obtained results. The ways of assessing the integral indicator of regional development are determined: determination of local factors of regional development; formation of general indicators of regional development; construction of a multi-level system of integrated assessment indicators; assessment of local factors using quantitative and qualitative methods; development of mathematical models for the assessment of generalizing factors; assessment of generalizing factors using the geometric mean method; construction of an integral model of assessment of regional development; determination of weight coefficients taking into account the corresponding stimulants; assessment of the integral indicator of regional development. As a result of the study, it was determined that the gross regional product index causes a change in the number of students in higher education institutions by 68%. It should be noted that other factors negatively affect the number of applicants. In the study, a mathematical toolkit is proposed, which allows you to form a quantitative basis for making management decisions. It was established that in the future, regional factors and demographic parameters lead to a decrease in the number of students in higher education institutions, which negatively affects the development of the educational system.